Efficacy and safety of latanoprost/timolol fixed combination dosed twice daily compared to once daily in patients with primary open angle glaucoma - Anis Baidura Azal; Siti Husna Hussein; Seng Fai Tang; Othmaliza Othman; Norshamsiah Md Din (International Journal of Ophthalmology (c/o Editorial Office), 2024)
International Journal of Ophthalmology Volume 16 No. 8 Page (1243-1249)